1994
DOI: 10.1128/jb.176.18.5686-5696.1994
|View full text |Cite
|
Sign up to set email alerts
|

A Saccharomyces cerevisiae mutant with echinocandin-resistant 1,3-beta-D-glucan synthase

Abstract: A novel, potent, semisynthetic pneumocandin, L-733,560, was Chem. 37:222-225, 1994). Glucan synthesis catalyzed by a crude membrane fraction prepared from the S. cerevisiae mutant R560-1C was resistant to inhibition by L-733,560. The nearly 50-fold increase in the 50% inhibitory concentration against glucan synthase was commensurate with the increase in whole-cell resistance. R560-1C was cross-resistant to other inhibitors of C. albicans 1,3-p-D-glucan synthase (aculeacin A, dihydropapulacandin, and others)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

7
119
0
2

Year Published

1995
1995
2015
2015

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 128 publications
(129 citation statements)
references
References 54 publications
7
119
0
2
Order By: Relevance
“…comm.). The etgl-1 mutant was isolated as a mutant resistant to L-733,560, a semisynthetic echinocandin [37], which inhibits fll,3-glucan synthase in Candida albicans [38]. In vitro, the ICso offl-glucan synthase activity to L-733,560 ofetgl-1 was found to be 50-fold higher compared to wild type, explaining the resistancy to L-733,560 in vivo, and indicating that C WH53/ETG1 is involved in the formation offl 1,3-glucan.…”
Section: Discussionmentioning
confidence: 99%
“…comm.). The etgl-1 mutant was isolated as a mutant resistant to L-733,560, a semisynthetic echinocandin [37], which inhibits fll,3-glucan synthase in Candida albicans [38]. In vitro, the ICso offl-glucan synthase activity to L-733,560 ofetgl-1 was found to be 50-fold higher compared to wild type, explaining the resistancy to L-733,560 in vivo, and indicating that C WH53/ETG1 is involved in the formation offl 1,3-glucan.…”
Section: Discussionmentioning
confidence: 99%
“…Early genetic studies by Myra Kurtz and Cameron Douglas (Merck Research Labs) with caspofungin in S. cerevisiae (Douglas et al, 1994a;Douglas et al, 1994b) and C. albicans indicated that Fks1, the major subunit of glucan synthase, is the presumed target of the echinocandins. These genetic studies suggested that target-site modification was a likely cause of reduced susceptibility.…”
Section: Fks1 Modification In Candida-a Mechanism For Clinical Drug Rmentioning
confidence: 99%
“…However, glucan synthase has been purified extensively from solubilized membranes by the product entrapment procedure (125). These preparations were enriched in the product of the FKS1 gene, which, together with its homologue, FKS2 (126), has been implicated in the activity of glucan synthase (127,128). Mutants in FKS1 were first isolated in a screen for hypersensitivity to immunosuppressants (129), and again, under the name etg1, in a screen for strains resistant to glucan synthase inhibitors (127).…”
Section: On the Nature Of The Direct Target Of Rho1 In The Glucan Synmentioning
confidence: 99%
“…These preparations were enriched in the product of the FKS1 gene, which, together with its homologue, FKS2 (126), has been implicated in the activity of glucan synthase (127,128). Mutants in FKS1 were first isolated in a screen for hypersensitivity to immunosuppressants (129), and again, under the name etg1, in a screen for strains resistant to glucan synthase inhibitors (127). Null ( f ks1 ) mutants show a decrease in glucan synthase activity (128) and in incorporation of glucose into β (1 → 3)glucan in vivo (130); double null ( f ks1 f ks2 ) mutants are inviable (126).…”
Section: On the Nature Of The Direct Target Of Rho1 In The Glucan Synmentioning
confidence: 99%